Green Accounting and Sustainable Finance: The Role of Tax Incentives - Nia Kurniati; Luis Santos; Maria Clara Reyes (Journal Markcount Finance, 2025)
Green accounting and sustainable finance have emerged as critical tools for promoting environmental sustainability and economic growth. Tax incentives are increasingly recognized as a key mechanism to encourage businesses to adopt green accounting practices and invest in sustainable projects. However, the effectiveness of tax incentives in driving sustainable finance remains underexplored, particularly in developing economies where environmental regulations are still evolving. This study aims to examine the role of tax incentives in promoting green accounting and sustainable finance, providing insights into how fiscal policies can support environmental sustainability. A quantitative research design was employed, utilizing data from 200 companies in Indonesia. Multiple regression analysis was used to analyze the relationship between tax incentives, green accounting practices, and sustainable finance indicators, such as green investments and carbon footprint reduction. The findings reveal that tax incentives significantly enhance green accounting practices and sustainable finance. Companies benefiting from tax incentives reported higher levels of green investments and greater reductions in carbon emissions. The study also found that firm size and industry type moderate this relationship, with larger firms and those in environmentally sensitive industries showing stronger responses to tax incentives. This study highlights the importance of tax incentives in driving green accounting and sustainable finance. The results suggest that policymakers should design targeted tax policies to encourage businesses to adopt environmentally sustainable practices and contribute to global sustainability goals.